PENGARUH PERUBAHAN BUDAYA TERHADAP KONSEPSI INOVASI KARYA BATIK PADA MASYARAKAT PENGRAJIN BATIK DESA PUNGSARI KECAMATAN PLUPUH KABUPATEN SRAGEN - Darwoto Darwoto (Canthing, 2020)
Batik is one of art form which is owned IndonesiaNation. In its development can not be separated fromthe influence of cultural change. Among of Batik creation is done by the batik painter who in fact theyare the farming society.Batik existing and developingat Pungsari village, Plupuh subdistrict, Sragen regency is one of batikwhich was born on the farming society. Batik in this area was born as a form of collective works basedon a concept and not a change in hereditary. As cultural products on the basis of its emergence as amajor manifestation of an embodiment of an agrarian society mired in economic terms, batik in thisarea was born and evolved into a vehicle for creative economy society that evolved into a new incomein the society.On the stage of its development as the influence of cultural change triggered the conception of thework as a form of innovation to maintain the product in the concept of marketing competition,defensing economy and improving the quality and quantity. This condition makes existence be able tocontinue surviving and developing well and also improving the society's economy. The other impactsis a change in the social construction of the form of order agrarian society to an industrial societyform.